Perkembangan Emosi Siswa Sekolah Dasar - Ali Muckromin; Murfiah Dewi Wulandari; Darsinah Darsinah (Jurnal Ilmiah Wahana Pendidikan, 2022)
One aspect that must be known by an elementary school teacher before carrying out the learning process is the emotional development of students, so that they can make lesson plans that are in accordance with their emotional conditions. Therefore, information is needed that discusses the emotional development of students in elementary schools. Writing of this article aims toward discuss of emotional development phase in elementary school students. Research method with a literature study of 15 journals related to the characteristics of the emotional development of elementary school students, which is then used as a reference to determine the characteristics of the emotional development of elementary school students. There are four aspects that can affect the emotional development of elementary school students, namely: student conditions, learning aspects, learning conditions as well as guidance and supervision in learning and the family environment.